Research Progress in Tunable Metamaterial Absorbers - Yixin Liu; Chenxia Li; Bo Fang; Liang Chen; Jianfeng Xu; Fuhai Liu; Lizhen Xu; Xiao Li; Ying Tang; Zhi Hong; Xufeng Jing (Advanced Photonics Research, 2024)
Since the initial discovery of metamaterial absorbers (MAs), they generate significant interest across the electromagnetic device industry due to their capacity to attain subwavelength magnitudes, adaptable design, and almost complete absorption. In recent years, there has been a growing focus on incorporating active materials into MAs, making it a current focal point of investigation. In the past few years, MAs have seen the integration of various active materials and configurations thanks to continuous exploration and innovation. Herein, comprehensive and systematic research on different tuning methods of MAs is reviewed, highlighting innovative materials and unique designs to accurately control the electromagnetic absorption characteristics of MAs. Key parameters, such as the operating frequency and relative tuning range, are summarized and compared to provide guidance for optimization design. Finally, the challenges of tunable MAs and their future prospects are also summarized.